FUNGSI KOORDINASI DINAS SOSIAL TERHADAP KECAMATAN DALAM PENANGGULANGAN KEMISKINAN DI ACEH BARAT - Sri Dwi Friwarti (Jurnal Ilmiah Peuradeun, 2014)
The provisions of Article 27 paragraph ( 3 ) of Government Regulation No. 19 Year 2008 concerning the District determined that the sub-district to coordinate with local work units within the district / city governments in the framework of the implementation of government activities in the district. The position of Social Service and the District both structurally regional work units. However, in the review of the rank of Head of Social class and sub-district has the distinction of class rank. The aim of this study wanted to see how the coordination function of the Department of Social Welfare in poverty districts in West Aceh and any obstacles encountered in implementing the Department of Social Welfare for Poverty Reduction. The method used is normative and sociological, and then analyzed using qualitative approaches are presented descriptively. The results showed that the coordination has not been implemented with what is expected. Obstacles encountered include the lack of a coordinated team of district -level poverty, the delegation of authority to the sub-district head has not been accompanied by adequate financing, the limited quality of personnel, facilities and infrastructure in the district.